Analysis of regional variation in levels of regional development using the principal components analysis method (PCA). The case of the northeastern region of Algeria - Bouziane, Asma; Benmissi, Ahcene (Technium Social Sciences Journal, 2022)
The northeastern region of Algeria, like the other Algerian regions, suffers from the problem of regional variation in the levels of development between the various states that make up it, as a result of not taking into account the spatial dimension in the previous development plans. This led to the emergence of clear imbalances, which affected the level of regional development. Therefore, this study aims to highlight this developmental imbalance by relying on natural, social and service indicators, which numbered 50 indicators. Using the principal components analysis method (PCA), which have the ability to reduce the variables to a limited number of factors, in order to highlight the most important variables that had a clear impact on this regional variation. The analysis produced seven main factors, where a large number of variables were associated with the first and second factors, which explained 60.67% of the total variance. The first factor explained 40.87% of the variance. It was linked to the variables related to the services and equipment index, and it included states with a good development level. the second factor explained 19.8% of the variance, and the variables related to the natural indicator were associated with it. It includes states with a medium development level, while the other states have a negative correlation with the first and second factor, and it is related to states with a weak development level, the study concluded that the region suffers from a developmental disparity between the various states that make up it. Therefore, the study recommended the necessity of including the regional dimension in planning, depending on the local capabilities of each state to eliminate regional disparity.